2018
DOI: 10.3389/fnmol.2018.00042
|View full text |Cite
|
Sign up to set email alerts
|

A Nogo-Like Signaling Perspective from Birth to Adulthood and in Old Age: Brain Expression Patterns of Ligands, Receptors and Modulators

Abstract: An appropriate strength of Nogo-like signaling is important to maintain synaptic homeostasis in the CNS. Disturbances have been associated with schizophrenia, MS and other diseases. Blocking Nogo-like signaling may improve recovery after spinal cord injury, stroke and traumatic brain injury. To understand the interacting roles of an increasing number of ligands, receptors and modulators engaged in Nogo-like signaling, the transcriptional activity of these genes in the same brain areas from birth to old age in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…In the adult animal, mature CNS networks are much more stable, optimized towards optimal information flow and function [ 40 ]. Expression of Nogo-A is highly region-specific and significantly altered from the developing stage to adulthood, especially in areas of the CNS with high plasticity [ 41 , 42 ], with the notable inclusion of the motor cortex layer 2/3 [ 32 , 38 ]. Further evidence for a stabilizing function of the Nogo signaling cascade is provided by findings that network connectivity failed to stabilize in Nogo receptor-deficient mice, resulting in expansion of the critical period into adulthood [ 16 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the adult animal, mature CNS networks are much more stable, optimized towards optimal information flow and function [ 40 ]. Expression of Nogo-A is highly region-specific and significantly altered from the developing stage to adulthood, especially in areas of the CNS with high plasticity [ 41 , 42 ], with the notable inclusion of the motor cortex layer 2/3 [ 32 , 38 ]. Further evidence for a stabilizing function of the Nogo signaling cascade is provided by findings that network connectivity failed to stabilize in Nogo receptor-deficient mice, resulting in expansion of the critical period into adulthood [ 16 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, lower cognitive performance correlated with lower RTN4 expression levels. Previously Nogo has been shown to have roles in several developmental and adult synaptic plasticity related processes in the brain, including cell migration, axon guidance, and myelination (Schmandke et al, 2014), and functions including memory and motor learning (Smedfors et al, 2018). In relation to the latter process, Nogo has been demonstrated to be involved in autoimmune-mediated demyelination, a failure of the axons to regenerate after neurodegenerative disorders or injury (Karnezis et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Myelin dysfunction has been suggested to be involved in pathogenesis of schizophrenia (Hakak et al, 2001), and a previous study has shown decreased serum expression levels of Nogo in schizophrenia patients (Demirel et al, 2017). In addition to schizophrenia, disturbed Nogo-signalling has been associated with other psychiatric and neurological diseases, and activity of the related genes has been shown to change from birth to old age (Smedfors et al, 2018). Within the probes associated with the factor Verbal working memory, one was representing the PTGER4 gene (prostagladin E receptor 4) (q = 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…ISVPs are characterized by an altered conformer of the σ1 protein and proteolytic removal of the σ3 protein, leading to the hypothesis that the virion conformer of σ1, outer-capsid protein σ3, or both engage NgR1. NgR1 is expressed in neural cells targeted by reovirus [31,[35][36][37] and interacts with a structurally diverse set of myelin inhibitory proteins to recruit multiple coreceptors, initiate signaling, and prevent neurite outgrowth [38][39][40][41]. There is limited structural information about how NgR1 coordinates binding to these diverse ligands and co-receptors to bring about its important functions.…”
Section: Introductionmentioning
confidence: 99%